Human Resource Excellence : An Assessment of Strategies and Trends - Lawler, Edward E. (Stanford University Press, 2020)
As a field, human resources has been slow to evolve, despite a great need and opportunity for change. Human Resource Excellence delivers the newest findings about what makes HR successful and how it can add value to today's organizations. Tracing changes in a global sample of firms across the US, Europe, and Asia, this landmark volume provides an international benchmark against which to measure a company's HR practice. For over twenty years, USC's Center for Effective Organizations has conducted the definitive longitudinal study of the human resource management function. Analyzing new data every three years, the Center charts changes in HR and offers guidance on how human resource professionals can drive firm performance. In this latest survey, Edward E. Lawler III and John W. Boudreau conclude that HR is most powerful when it plays a strategic role, makes use of information technology, and has tangible metrics and analytics. Their insights offer an essential understanding of HR's changing role in strategy, big data, social and knowledge networks, and the gig economy.